2015
DOI: 10.2105/ajph.2015.302890
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Public Open Spaces and Recreational Walking

Abstract: Building 1 high-quality local park may be more effective in promoting recreational walking than is providing many average-quality parks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 26 publications
1
46
0
5
Order By: Relevance
“…However, more evidence is required to explore what role small parks play (if any) and for whom, and how the quality of smaller parks affects both physical activity and mental health outcomes ( Francis et al 2012 ). In the meantime, given the exponential growth of cities around the globe and global targets to increase access to public open space, both our longitudinal and cross-sectional findings suggest that fewer larger open spaces may be preferable than providing many small public open spaces ( Sugiyama et al 2010 , 2015 ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, more evidence is required to explore what role small parks play (if any) and for whom, and how the quality of smaller parks affects both physical activity and mental health outcomes ( Francis et al 2012 ). In the meantime, given the exponential growth of cities around the globe and global targets to increase access to public open space, both our longitudinal and cross-sectional findings suggest that fewer larger open spaces may be preferable than providing many small public open spaces ( Sugiyama et al 2010 , 2015 ).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, recreational walking may increase over time as these positive perceptions grow. A previous cross-sectional study of RESIDE participants highlighted the importance of the quality of neighborhood environments ( Sugiyama et al 2015 ). This study found that walking to local public open space was associated with public open spaces being attractive with gardens, grassed areas, walking paths, water features, wildlife, amenities, dog-related facilities, and off-leash areas for dogs ( Sugiyama et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our components of walkable urban form do not include other environmental aspects such as surface condition or route aesthetics that may relate to walking behaviour [59]. Similarly, this study considers POS in terms of count, area, and greenness; it does not include other features relating to POS quality that may influence behaviour and health outcomes [60]. The environmental characteristics assessed may have changed during the cohort follow-up period, however there was little evidence of area gentrification during this time period [61].…”
Section: Discussionmentioning
confidence: 99%
“… 5 Previous studies have indicated that people with access to walking loops were more likely to engage in moderate to vigorous physical activity. 6 …”
mentioning
confidence: 99%